Muslim Non-Cash Transaction Behavior: The Moderating Role of Religiosity - Chindy Chintya Cahya; Khoirul Umam (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Despite years of exploration, empirical evidence regarding the mediating role of religiosity in the relationship between non-cash interest and behavior is still lacking. This study analyzed the behavior related to the use of non-cash transactions by Muslim communities moderated by religiosity based on the TAM model. The sampling technique in this study used purposive sampling with a total of 438 respondents. The data in this study were analyzed using Partial Least Square Structural Equation Model (PLS-SEM) with Smart PLS 3.0. The results of this study reveal that religiosity can moderate the interest and behavior of using non-cash transactions. Besides that, the perceived ease of use and perceived usefulness have a significant positive effect on consumer behavior in using non-cash transactions, which are proxied by attitude and interest. These results indicate that the Muslim community is accepting and even supporting the development of technology in the payment system because technology brings convenience and benefits. As a result, players in the Islamic finance and halal market should pay close attention to the advancements in payment system technology to ensure the Muslim community prefers payment products on the Sharia market.